Perilaku Hidup Bersih Dan Sehat di Ra At Thoyyibah Singogalih Tarik Sidoarjo - Dini Rofi’atin Husna (Perkumpulan Dosen Program Hibah Indonesia (PDPHI), 2024)
This study aims to examine the application of Clean and Healthy Living Behavior (PHBS) in early childhood at RA At Thoyyibah Singogalih Tarik Sidoarjo. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews with teachers and parents, and documentation of learning activities. The results showed that the school has carried out various efforts in familiarizing children to apply PHBS, such as washing hands with soap, maintaining personal and environmental hygiene, and educating healthy food consumption. The role of teachers is very important in guiding and supervising these habits, including through the integration of religious values as additional motivation. Nevertheless, there are still challenges in the form of limited hygiene facilities and children's lack of understanding of the importance of PHBS. This study confirms that the successful implementation of PHBS requires the support of a conducive environment and the active involvement of all parties, including parents. The findings provide practical recommendations for other educational institutions to develop effective and sustainable PHBS programs, taking into account the cultural context and local needs.